The Multifaceted Activity of the VirF Regulatory Protein in the Shigella Lifestyle - Di Martino, Maria Letizia; Falconi, Maurizio; Micheli, Gioacchino; Colonna, Bianca; Prosseda, Gianni (Frontiers in Molecular Biosciences, 2016)
Shigella is a highly adapted human pathogen, mainly found in the developing world and causing a severe enteric syndrome. The highly sophisticated infectious strategy of Shigella banks on the capacity to invade the intestinal epithelial barrier and cause its inflammatory destruction. The cellular pathogenesis and clinical presentation of shigellosis are the sum of the complex action of a large number of bacterial virulence factors mainly located on a large virulence plasmid (pINV). The expression of pINV genes is controlled by multiple environmental stimuli through a regulatory cascade involving proteins and sRNAs encoded by both the pINV and the chromosome. The primary regulator of the virulence phenotype is VirF, a DNA-binding protein belonging to the AraC family of transcriptional regulators. The virF gene, located on the pINV, is expressed only within the host, mainly in response to the temperature transition occurring when the bacterium transits from the outer environment to the intestinal milieu. VirF then acts as anti-H-NS protein and directly activates the icsA and virB genes, triggering the full expression of the invasion program of Shigella. In this review we will focus on the structure of VirF, on its sophisticated regulation, and on its role as major player in the path leading from the non invasive to the invasive phenotype of Shigella. We will address also the involvement of VirF in mechanisms aimed at withstanding adverse conditions inside the host, indicating that this protein is emerging as a global regulator whose action is not limited to virulence systems. Finally, we will discuss recent observations conferring VirF the potential of a novel antibacterial target for shigellosis.